Malignant pleural mesothelioma with rarely seen metastases - Elif Şenocak Taşçı; Gül Akın; Birgül Öneç; Onur Eşbah (Journal of Oncological Sciences, 2017)
Malignant mesothelioma, primarily located in the pleura, is a locally aggressive tumor. Distant metastases are rarely seen and mostly diagnosed postmortem. We present the third malignant pleural mesothelioma (MPM) case in the literature with bone marrow metastasis. A 36-year-old male patient presented with pain at the right mediastinal area and 5 × 6cm mass on the right side of his chest. 18-FDG positron emission tomography (PET) scan showed local uptake at the pleura, regional lymph nodes and 5th rib. The tru-cut biopsy reported as sarcomatoid type MPM. Cisplatin-pemetrexed therapy was planned. His medical condition deteriorated after 2 months and multiple metastases to brain, liver, adrenal glands and bone marrow were detected. The patient was lost 4 months after he was diagnosed. Brain and bone marrow metastasis of MPM are rarely seen. Physicians should be careful about the rapid progression and unexpected metastases of MPM.